Serum IL-21 and IFN-γ Levels in Celiac Disease and Their Association with Biochemical Indicators - Noor H. Al-Mousawi (Academia Open, 2025)
Background : Celiac disease (CD) is an autoimmune disorder that is mainly specific to the small intestine and is caused by an abnormal T-cell-mediated immune response to dietary gluten which involves mucosal inflammation and villous atrophy. Activation of the systemic immunology has the potential of causing extra-intestinal symptoms. Objective: The levels of serum IL-21 and IFN-g of the celiac disease patients were determined in this study and the levels were compared to the level of biochemical parameters like hemoglobin, ferritin, calcium, and vitamin D3. Methods: A total of 70 clinically proven celiac patients (9-74 years old) were recruited in Wasit hospitals at a time period of March 2024 to April 2025. Venous blood samples were collected using the enzyme-linked immunosorbent test (ELISA), centrifuged and analyzed with regard to the levels of IL-21 and IFN-g. Measurement of biochemical parameters was done using automated analyzers in accordance to the conventional protocols. Results: Celiac patients had much higher serum concentrations of IFN-g and IL-21 in comparison to healthy controls (p < 0.001). All the levels of vitamin D3, calcium, iron, ferritin, and hemoglobin were lowered significantly (p < 0.05). These biological markers were found to have negative relationships with cytokines. Conclusion: In celiac disease, immune activation is manifested by increased levels of IL-21 and IFN-g, which can be one of the causes of intestinal damage and nutrient loss. Also, findings indicate immunopathological and not diagnostic relations between biochemical deficits and cytokine imbalance.Highlight : Stress strongly predicts insomnia in celiac patients. Persistent symptoms also contribute to insomnia. Diet quality is not related to insomnia. Keywords : Celiac Disease , Anti-Tissue Transglutaminase, cytokines, IL-21, IFN-γ.